Renal Leiomyosarcoma, a Rare Presentation - Toukilnan Djiwa; Kossi Akomola Sabi; Panakinao Simgban; Mayi Bombonne; Bagassam Mézéwè Sama; Mazamaesso Tchaou; Tchin Darré (Journal of Kidney Cancer and VHL, 2022)
Renal sarcomas are very rare malignant tumours with a very poor prognosis. Renal leiomyosarcoma, a malignant tumour of smooth muscle origin, is the most common histological type. The article reports a case of leiomyosarcoma of renal location, with a review of the literature. A 38-year-old female patient, with no previous pathological history, consulted the nephrology department of the Teaching Hospital of Lomé for abdominal pain that had been present for 4 years. Histology showed a tumour proliferation of fasciculated architecture, made of spindle cells arranged in long bundles, with cytonuclear atypia and cytoarchitectural abnormalities. Immunohistochemical examination showed positive staining for smooth muscle actin, h-caldesmone, desmin and CD34 and negative for pancytokeratin (AE1/AE3), myogenin and PS100. Renal leiomyosarcoma is an exceptional malignancy. It remains the most common renal sarcoma, the differential diagnosis of which is based on immunohistochemical findings.